The reliability of a maximal isometric hip strength and simultaneous surface EMG screening protocol in elite, junior rugby league athletes - Charlton, P. C.; Mentiplay, B. F.; Grimaldi, A.; Pua, Y.-H.; Clark, R. A. (Journal of Science and Medicine in Sport, 2017)
Objectives: Firstly to describe the reliability of assessing maximal isometric strength of the hip abductor and adductor musculature using a hand held dynamometry (HHD) protocol with simultaneous wireless surface electromyographic (sEMG) evaluation of the gluteus medius (GM) and adductor longus (AL). Secondly, to describe the correlation between isometric strength recorded with the HHD protocol and a laboratory standard isokinetic device. Design: Reliability and correlational study. Methods: A sample of 24 elite, male, junior, rugby league athletes, age 16-20 years participated in repeated HHD and isometric Kin-Com (KC) strength testing with simultaneous sEMG assessment, on average (range) 6 (5-7) days apart by a single assessor. Strength tests included; unilateral hip abduction (ABD) and adduction (ADD) and bilateral ADD assessed with squeeze (SQ) tests in 0 and 45° of hip flexion. Results: HHD demonstrated good to excellent inter-session reliability for all outcome measures (ICC(2,1) = 0.76-0.91) and good to excellent association with the laboratory reference KC (ICC(2,1) = 0.80-0.88). Whilst intra-session, inter-trial reliability of EMG activation and co-activation outcome measures ranged from moderate to excellent (ICC(2,1) = 0.70-0.94), inter-session reliability was poor (all ICC(2,1) < 0.50). Conclusions: Isometric strength testing of the hip ABD and ADD musculature using HHD may be measured reliably in elite, junior rugby league athletes. Due to the poor inter-session reliability of sEMG measures, it is not recommended for athlete screening purposes if using the techniques implemented in this study. AUTORREFERAT